Extensive Right Pleural and Chest Wall Malignant Fibrous Histiocytoma at an Unusual Age: Computed Tomography Features (2015)
Aims: To describe a rare case of malignant fibrous histiocytoma at an unusual age of sixteen (16) years. Also to sensitize the medical community to the need for thorough evaluation of an opaque hemithorax and to describe the imaging features of this rare neoplastic disease. Presentation of Case: This was a 16 year old girl who presented with progressive swelling and recurrent right chest pain of 10 months duration and difficult breathing of 6 weeks duration. There was associated weight loss, dry cough and low grade intermittent fever. She had solitary cervical lymphadenopathy, grade II finger clubbing and low hematocrit. Discussion: Malignant fibrous histiocytomas (MFHs) are tumors of adulthood with a mean age of 59 years. It has predilection for the extremities, the abdominal cavity and the retroperitoneum. Primary pleural occurrence is relatively rare. This is a rare case of an extensive malignant fibrous histiocytoma of the right pleura with chest wall involvement presenting at an unusual young age of 16 years, at variance with the ages documented in the literatures. Imaging findings of the histologically proven tumor were also described on high resolution chest Computed Tomography. Conclusion: Malignant fibrous histiocytomas may occur much earlier than the age documented in most literatures. This case showed that not all cases of extensive opaque hemithorax are due to massive pleural effusion and further and better diagnostic imaging will be necessary for prompt and proper management.